Management of complication of type Fugazzotto I for the maxillary sinus lift with inlay bone graft - Reyes Doimi, Juan Domingo (2017)
Perforations produced during the manipulation of the Schneiderian membrane on sinus lift procedures are common in our practice. That is the reason why a new alternative is suggested in this article for sinus lift membrane perforations. On this case, a Fugazzotto type I perforation happened at the moment of the placement of an inlay block bone xenograft. This technique is predictable and optimal for fixing membrane ruptures during surgery